Child and Parent Demographic Characteristics and Oral Health Perceptions Associated with Clinically Measured Oral Health. (July 2018) - Marcus, M.; Maida, C.A.; Wang, Y.; Xiong, D.; Hays, R.D.; Coulter, I.D.; Lee, S.Y.; Spolsky, V.W.; Shen, J.; Crall, J.J.; Liu, H.
Objective: To examine child and parent reports about the child's oral health and assess the associations of these reports with clinical assessments of oral health status by dental examiners. Methods: Surveys with 139 items for children and 133 items for parents were administered by Audio Computer-Assisted Self-Interview Software. In addition, the Children's Oral Health Status Index (COHSI) was computed from a dental examination. Results: A total of 334 families with children ages 8 to 17 y participated at 12 dental practices in Los Angeles County. Ordinary least squares regression models were estimated separately for child and parent surveys to identify items uniquely associated with the COHSI. Ten of 139 items the children reported regarding their oral health were associated with the COHSI. The strongest associations were found for child's age, aesthetic factors (straight teeth and pleased with teeth), and cognitive factors related to perception of dental appearance (pleased/happy with the look of the child's mouth, teeth, and jaws). Nine of 133 parent items about the child's oral health were associated with the COHSI in the parent model, notably being a single parent, parent's gender, parent born in the United States, pleased or happy with the look of their child's teeth, and accessing the Internet. Conclusion: These child and parent survey items have potential to be used to assess oral health status for groups of children in programs and practices in lieu of dental screenings. Knowledge Translation Statement: The paper's results inform the development of a toolkit that can be used by schools, public health agencies, and dental programs to identify children with low oral health status based on parents' and children's responses to survey items across demographic, physical, mental, and social domains. These survey items can be used to inform parents of the desirability of proactively addressing inadequacies in their child's oral health status, enabling them to more rationally address dental needs.